A qualitative study on the factors affecting the valuation of football players in Europe - Kowlessur, Manu (2021)
Football players have seen their market values increase drastically over the years. They have seen their importance grown in the books of football clubs and with the advancement of technology and analysis of football players both on and off the pitch, variables also known as factors have influenced their market values. The study provides for an in-depth analysis of the transfer market especially from 1990 onwards which represent the period from when transfer fees skyrocketed and the analysis of the current factors that have been found to have more effect on football players valuations. Furthermore, the research also discusses about other factors which may impact valuation calculations and recommendations on how the other factors should be considered and evaluated as well as the implementation of a regulation.